2022
DOI: 10.1186/s40643-022-00540-4
|View full text |Cite
|
Sign up to set email alerts
|

A facile and robust T7-promoter-based high-expression of heterologous proteins in Bacillus subtilis

Abstract: To mimic the Escherichia coli T7 protein expression system, we developed a facile T7 promoter-based protein expression system in an industrial microorganism Bacillus subtilis. This system has two parts: a new B. subtilis strain SCK22 and a plasmid pHT7. To construct strain SCK22, the T7 RNA polymerase gene was inserted into the chromosome, and several genes, such as two major protease genes, a spore generation-related gene, and a fermentation foam generation-related gene, were knocked out to facilitate good ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…As shown in Figure S8, analysis of total intracellular protein by SDS-PAGE revealed that sfGFP was the most highly expressed protein in strains containing the T7-BOOST system in the low-copy-number plasmids, which is consistent with previous studies that expressed GFP in the genome or low-copy-number plasmid. 20,22 In the strain containing pHT-P T7lac , the sfGFP content and concentration were 19.4% and 0.18 g/L, and in the strain containing pHT-P T7xyl , the sfGFP content and concentration were 12.1% and 0.14 g/L, respectively. In order to assess potential misunderstandings regarding the characteristics of the expression systems, we randomly selected 20 colonies following the transformation of the plasmids depicted in Figure 3 into their respective B. subtilis strains.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure S8, analysis of total intracellular protein by SDS-PAGE revealed that sfGFP was the most highly expressed protein in strains containing the T7-BOOST system in the low-copy-number plasmids, which is consistent with previous studies that expressed GFP in the genome or low-copy-number plasmid. 20,22 In the strain containing pHT-P T7lac , the sfGFP content and concentration were 19.4% and 0.18 g/L, and in the strain containing pHT-P T7xyl , the sfGFP content and concentration were 12.1% and 0.14 g/L, respectively. In order to assess potential misunderstandings regarding the characteristics of the expression systems, we randomly selected 20 colonies following the transformation of the plasmids depicted in Figure 3 into their respective B. subtilis strains.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…18−20 In a recent study, the supercompetent SCK6 strain was utilized as the starting strain to establish the T7 expression system. 22 To enhance expression efficiency during high-density cell fermentation, two major protease genes (aprE and nprE), as well as genes associated with sporulation and fermentation foam generation (spoIIAC and srfAC), were knocked out. T7RNAP integration was accomplished through a plasmid-based approach, resulting in a T7 expression system that can be easily transferred to any other B. subtilis strain in a plug-and-play manner.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recombinant enzymes αGP, phosphoglucomutase (PGM), phosphoglucose isomerase (PGI), tagatose 6-phosphate 4-epimerase (TPE), and tagatose 6-phosphate phosphatase (T6PP) were individually expressed in B. subtilis SCK 22 . TEOS and APTES were purchased from Shanghai McLean Biochemical Technology Co. Ltd. (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…A recombinant PGM from E. coli has also been used to enhance UDP-galactose derived synthesis of the bioactive compound hyperoside (quercetin 3-O-galactoside) in a metabolically engineered E. coli strain (Li et al, 2022). In addition, PGM from T. kodakarensis has recently been heterologously expressed in B. subtilis thereby allowing for the recombinant enzyme to be produced at high levels in highdensity fermentations for subsequent potential synthesis of inositol from starch (Ye et al, 2022). Increased expression of PGM to generate increased polysaccharide production has recently been achieved in the fungus Cordyceps militaris, with homologous overexpression of PGM and UDP-glucose 6-dehydrogenase in the fungus resulting in an approximately 78% increase in polysaccharide levels.…”
Section: Biotechnological Potentialmentioning
confidence: 99%